Client Server Based Integrated School System Design and Implementation - M. Fauzi Natsir (Arkus, 2020)
The integrated school system is an application intended to process school data, such as processing student re-registration data, student attendance data, and student payment data. This data is not yet optimal, causing difficulties in finding information about student data and making reports that are not adequate. Therefore, an application that can support and solve these problems is needed. This application is built using the Apache webserver as the web server, using PHP as the programming language, and MySQL in database development. This study aims to design an integrated school system at SMAN 9 Makassar based on client-server. The type of research used is quantitative research, while data collection uses library research methods and field research (observation). The testing method uses black box testing, which focuses on the functional requirements of the software. With the integrated school system at SMAN 9 Makassar based on client-server, it can help staff and employees at SMAN 9 Makassar in terms of managing data related to the school. For example, in managing academic data, finance, libraries, personnel, teacher info, student info, and counseling agency.